2006
DOI: 10.1115/1.2241685
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Impact Test for Determining “Health” of Percutaneous Bone Anchored Implants

Abstract: There is an ongoing requirement for a clinically relevant, noninvasive technique to monitor the integrity of percutaneous implants used for dental restorations, bone-anchored hearing aids, and to retain extra-oral prostheses (ear, eye, nose, etc). Because of the limitations of conventional diagnostic techniques (CT, MRI), mechanical techniques that measure the dynamic response of the implant-abutment system are being developed. This paper documents a finite element analysis that simulates a transient response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Furthermore, their study showed that the relationship between the bone density and stress in the bone surrounding the implant is inversely proportional to each other, which means that, as the bone density decreases, the mechanical stresses in the surrounding bone increases. To model different interfacial conditions between the implant and bone, Jones et al (2006), develop contact elements by correlating the modeling to the measured dynamic responses. In a more recent study, Perez et al (2008) developed a phenomenological interface model to simulate the mechanical effects of the osseointegration process at the bone-implant interface by correlating with experimental results in rabbits, where a significant increase in resonance frequency was obtained as positive osseointegration progresses.…”
Section: Relationship Between Bone Density and Young's Modulusmentioning
confidence: 99%
“…Furthermore, their study showed that the relationship between the bone density and stress in the bone surrounding the implant is inversely proportional to each other, which means that, as the bone density decreases, the mechanical stresses in the surrounding bone increases. To model different interfacial conditions between the implant and bone, Jones et al (2006), develop contact elements by correlating the modeling to the measured dynamic responses. In a more recent study, Perez et al (2008) developed a phenomenological interface model to simulate the mechanical effects of the osseointegration process at the bone-implant interface by correlating with experimental results in rabbits, where a significant increase in resonance frequency was obtained as positive osseointegration progresses.…”
Section: Relationship Between Bone Density and Young's Modulusmentioning
confidence: 99%